Ultrafast and Reproducible Synthesis of Tailor-Made Octacalcium Phosphate - Choudhary, Rajan; Indurkar, Abhishek; Rubenis, Kristaps; Grava, Andra; Dubnika, Arita; Hurle, Katrin; Locs, Janis (ACS Omega, 2024)
Octacalcium phosphate (OCP) has excellent bone formation ability and a good resorption rate as compared to the commercial bone substitutes [e.g., Bio-Oss (Geistlich Pharma AG) and MBCP+ (Biomatlante)], as well as synthesized biomaterials (hydroxyapatite and tricalcium phosphate). The synthesis approach to obtain phase-pure OCP possesses a great challenge due to its complex reaction mechanism and narrow synthesis window. Thus, the current study aimed to overcome the synthesis challenges and to define the precise reaction conditions required for controllable and reproducible synthesis of OCP. Using the principles of the coprecipitation method, novel synthesis protocols were developed ensuring ultrafast synthesis of OCP within minutes. XRD analysis confirmed that phase-pure OCP was obtained. These processing schemes enabled the synthesis of tailor-made OCP with specific surface areas ranging from 16 to 91 m2/g. The synthesized OCPs exhibited plate-like morphology. The interaction of the synthesized OCPs with MC3T3-E1 cells was found to be nontoxic, confirming their cytocompatibility. The synthesis approach developed in this study indicates that challenges such as the reaction volume, stirring rate, and flow rate need to be addressed in the future to upscale the technology.
CRIS-Team Scopus Importer:2024-08-23